2022
DOI: 10.3390/ijerph191710878
|View full text |Cite
|
Sign up to set email alerts
|

Factor Analysis Affecting Degree of Depression in Family Caregivers of Patients with Spinal Cord Injury: A Cross-Sectional Pilot Study

Abstract: This study was conducted to determine the degree of depression in family caregivers of spinal-cord-injury patients and to identify factors influencing family caregivers’ depression. The final study subjects were 30 (family caregivers: 6 males and 24 females). The CES-D of family caregivers; general characteristics of spinal-cord-injury patients and family caregivers; and information on physical health, household income, leisure, social activity, family relationship, and life-in-general status of family caregiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 24 publications
0
0
0
Order By: Relevance
“…Shi et al [25] indicated that travelers with disabilities have their own unique motivations, and concluded they consider travel a way to regain independence, which would help satisfy the psychological need for autonomy. Important motivational forces in travel, leisure, and sport participation for PwSCI include demonstrating skill (where the psychological need for competence could be fulfilled) and bringing them in contact with others [26,27] and better connecting with their family members [28] (where the psychological need for relatedness could be satisfied). Tourism for PwSCI is also regarded as a complex interaction among factors of body function, activity participation, and the environment, where some assume that this population may need to sacrifice travel regardless of their sense of competence or motivation [29].…”
Section: Self-determination Theory Applications In Travel Participati...mentioning
confidence: 99%
“…Shi et al [25] indicated that travelers with disabilities have their own unique motivations, and concluded they consider travel a way to regain independence, which would help satisfy the psychological need for autonomy. Important motivational forces in travel, leisure, and sport participation for PwSCI include demonstrating skill (where the psychological need for competence could be fulfilled) and bringing them in contact with others [26,27] and better connecting with their family members [28] (where the psychological need for relatedness could be satisfied). Tourism for PwSCI is also regarded as a complex interaction among factors of body function, activity participation, and the environment, where some assume that this population may need to sacrifice travel regardless of their sense of competence or motivation [29].…”
Section: Self-determination Theory Applications In Travel Participati...mentioning
confidence: 99%